A Generative Learning Strategy-Based Program to Develop EFL Vocabulary and Oral Performance Skills of Al-Azhar Secondary Stage Students - بركات، إسلام محمد عليان; حسن، محمد حسن إبراهيم (جامعة الزقازيق - كلية التربية, 2024)
استهدفت الدراسة، تعرف فعالية برنامج مقترح قائم على استراتيجية التعلم التوليدي في تنمية الثروة المفرداتية ومهارات الأداء الشفهي بالإنجليزية لدى طلاب المرحلة الثانوية الأزهرية، ولتحقيق هذا الغرض تم إعداد قائمة بمهارات الأداء الشفهي الضرورية لطلاب الصف الأول الثانوي الأزهري، واختبار معرفي في الأداء الشفهي، ومعيار لتصحيح الاختبار، واختبار معرفي للمهارات المعجمية، وإعداد مواد المعالجة التجريبية المتمثلة في البرنامج المقترح المقدم وفق استراتيجية التعلم التوليدي. وقد استخدمت الدراسة المنهج شبة التجريبي لمجموعتين تجريبية وضابطة ذو الاختبارين القبلي والبعدي؛ حيث تم اختيار مجموعة من طالبات الصف الأول الثانوي الأزهري، بمعهد فتيات شرقية مباشر بإدارة الإبراهيمية التعليمية الأزهرية، محافظة الشرقية، وتم توزيعهم عشوائيا على مجموعتي الدراسة؛ المجموعة التجريبية (٢٥ طالبة)، والمجموعة الضابطة (٢٥ طالبة)، واستمرت الدراسة سبعة أسابيع خلال الفصل الدراسي الأول من العام الدراسي ٢٠٢٢ – ٢٠٢٣ م، وخلال هذه الفترة تم تدريب طالبات المجموعة التجريبية على المهارات المستهدفة من خلال برنامج مقترح قائم على استراتيجية التعلم التوليدي، في حين لم تتلق المجموعة الضابطة أية معالجة. وبعد دراستهن للبرنامج، وتطبيق أدوات الدراسة بعديا توصلت الدراسة إلى وجود فرق ذو دلالة إحصائية في الثروة المفرداتية، ومهارات الأداء الشفهي لصالح المجموعة التجريبية في التطبيق البعدي، مما يشير إلى فاعلية البرنامج المقترح في الثروة المفرداتية، ومهارات الأداء الشفهي بالإنجليزية لدى عينة الدراسة. The current study was carried out to investigate the effectiveness of utilizing a generative learning strategy-based program in fostering the targeted EFL lexical and oral performance skills among Al-Azhar secondary stage students. To attain the purpose of the study, the Quasi-experimental method was adopted with its pretest-posttest control /experimental groups design. Participants of the study consisted of (N=50) EFL students enrolled in the first-year Al-Azhar secondary stage, El-Sharkia Institute for girls, El-Ibrahimiya Educational Directorate, Sharkia Governorate during the first semester of the academic year 2022/2023. They were chosen and divided into two groups: treatment group (n=25), and non-treatment group (n=25). An EFL oral performance questionnaire accompanied with a scoring rubric, a pre-post oral performance test (OPT) and a pre-post lexical skills test (LST) were used as instruments of the study. The targeted EFL lexical and oral performance skills for 1st year secondary school students were determined to be enhanced through the use of a checklist approved by a jury of specialists in teaching EFL. Results revealed that there was a statistically significant difference between the mean scores of the treatment group in the pre-and post-administrations in both EFL lexical and oral performance skills, favoring the post- administrations. The findings of the study also revealed that the program based on the generative learning strategy had a positive effect on developing the EFL first-year secondary stage students' lexical and oral performance skills.
Keywords: الاستراتيجيات التعليمية -- الأداء الشفهي -- اللغة الإنجليزية -- التعليم الأزهري -- طلبة المدارس